A Qualitative Case Study of School Dropout Among the Laut Ethnic Group in Kampung Baru, Tajur Biru Village, Lingga Regency, Riau Islands, Indonesia - Karini; Kartini Sri Rahayu; Amanda Junianti; Marisa Elsera (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
This qualitative case study aims to analyze the factors contributing to school dropout among children from the Laut ethnic group in Kampung Baru, Tajur Biru Village, Lingga Regency. Data were collected through in-depth interviews with five informants, comprising two community leaders and three school dropouts, as well as field observations and documentation. The findings indicate that school dropout among Laut children is a multidimensional phenomenon influenced by interconnected economic, cultural, familial, and social factors. The primary contributing factors include the economic instability of traditional fishing households, limited parental awareness of the importance of formal education, and strong maritime cultural values that prioritize seafaring skills over schooling. Furthermore, stigma, discriminatory treatment, and social labeling within the school environment create psychological pressure and social exclusion, increasing the likelihood of students leaving school prematurely. The study recommends strengthening household economic resilience, expanding scholarship opportunities, and promoting inclusive, stigma-free school environments to reduce school dropout and improve educational participation among the Laut ethnic community.